DESIGN OF SUPPORT ON RAIL CARRIER FOR 50 METER LONG R60 RAIL TRANSPORTATION - Kenneth Tandri, Ignatius
There are two backgrounds for this study. First, the available regulation for rail carrier in Indonesia is only for 25 meter long rail. Second, Kereta Cepat Jakarta – Bandung project requires rail transportation facility for 50 meter long. The aim of this study is to design a support on rail carrier for 50 meter long rail transportation. This study is expected to become the recommendation for 50 meter long rail transportation regulation in Indonesia and help the Kereta Cepat Jakarta – Bandung project. This study used finite element method to analyze the safety factor and life cycle of the design. There are three design with different characteristic modelled and analyzed. Static and fatigue loading simulation to analyze these design is conducted using SolidWorks 2019. The results is validated by checking the convergence of the stresses. Based on the simulation result, the second design is better than the other two design. These three design each have high life cycle, but the third design does not have high safety factor. The first and second design have similar factor of safety, with only 0.028 in diversity. But, the mass and material cost of the second design are 38.9% lower than the first design. Thus, the final outcome of this study is the second design, which has safety factor of 1.679 and 51,960 life cycles.